Pengembangan Produk Promosi Perpustakaan Berbasis Video Animasi 2D di Perpustakaan SMA Negeri 8 Malang - Septiani Rosyidah; Kusubakti Andajani; Moh. Safii (Universitas Negeri Malang, 2021)
Abstract: Library plays a role as a learning resource center for school residents by providing library materials to support learning. However, the school library is underutilized properly as a learning support. The purpose of this research and development is to produce 2D animation video-based library promotion products that meet the aspects of feasibility, accuracy, and attractiveness. 2D animated video products are made with reading benefit materials and a 15-minute reading program in schools. This study used a research and development model for R&D Borg and Gall. The procedure or steps for media development go through four stages, namely: (1) the pre-development (preparation) stage, (2) the product development stage, (3) the product trial stage, and (4) the post-development stage. The finished 2-dimensional animated video product is then validated by media experts, material experts, librarians. The finished product is then tested on 30 students of SMA Negeri 8 Malang. The results showed that the assessment of media experts, material experts, and librarians gave the criteria